Znaczenie polskiej grupy wsparcia dla rodziców dzieci z niepełnosprawnościami i zaburzeniami mieszkających w Wielkiej Brytanii objętych angielskim systemem nauczania na przykładzie działalności „Wagonika Integracyjnego – grupy wsparcia dla Rodziców Dzieci o Specjalnych Potrzebach Eduakcyjnych" - Gołąbek-Jonak, Patrycja (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article presents the significance of the operating in Great Britain Polish support group“Wagonik Integracyjny - support group for Parents of Children with Special Educational Needs” for the parents of children with disability and disorders participating in English education system. The article consists of four parts. The first part concerns social support, it defines the term and describes its types. Part Two describes the English special education system for children and adolescents. Part three presents the activities of the support group “Wagonik Integracyjny - support group for Parents of Children with Special Educational Needs” since its inception. Part four refers to the problems that parents of children with disability and disorders in Great Britain who are members of the support group have to face.This part also draws attention to the important role of the “Wagonik Integracyjny” in solving associated problems and describes the forms of support it offers to its participants.